The Financial Advisor M&A Guidebook Best Practices, Tools, and Resources for Technology Integration and Beyond - Friedman, Greg (Springer International Publishing, 2018)
With M&As in the RIA space increasing, many firms are rapidly changing hands with little to no expert guidance on how to successfully execute a merger or acquisition. In 2017, a record number of M&A deals closed in the advisor space - 168 transactions, or a 22% growth over 2016. Aside from a fifth straight year of record highs in M&A activity, the size of the acquired firms has also increased, with average acquisitions involving wealth managers exceeding $1.01 billion in assets under management. For many advisors, it only takes a handful of missteps during a merger or acquisition to jeopardize their business, but with so much unknown, advisors need a guidebook for success. A significant and often overlooked component to a successful RIA merger or acquisition is the thoughtful integration of technology. This comprehensive guide walks you through the steps of strategy, assessment, implementation, adoption and growth, all while considering how to best inspire and galvanize a firm's most valuable asset - its people. Combining the real-life experiences of a life-long financial advisor with the expertise of a 15-year operations director and founder of a large RIA ops network, this book takes real M&A experiences of the financial services industry and offers best practices, tools and resources to help advisors make smart decisions about technology integration that elevates the firm's goals and solidifies its future success. .